Using Nudges to Enhance Clinicians' Implementation of Shared Decision Making With Patient Decision Aids. Issue 1 (April 2020) - Kostick, Kristin M.; Trejo, Meredith; Volk, Robert J.; Estep, Jerry D.; Blumenthal-Barby, J.S.
Background. Although effective interventions for shared decision making (SDM) exist, there is a lack of uptake of these tools into clinical practice. "Nudges, " which draw on behavioral economics and target automatic thinking processes, are used by policy makers to influence population-level behavior change. Nudges have not been applied in the context of SDM interventions but have potential to influence clinician motivation, a primary barrier to long-term adoption of SDM tools.Objective. Describe, evaluate, and propose recommendations for the use of a behavioral economics framework (MINDSPACE) on clinician motivation and behavior during implementation of a validated decision aid (DA) for left ventricular assist device at nine hospitals.Methods. Qualitative thematic analysis of process notes from stakeholder meetings during the first 6 months of implementation to identify examples of how the MINDSPACE framework was operationalized. Quantitative implementation progress was evaluated using the RE-AIM framework.Results. MINDSPACE components were translated into concrete approaches that leveraged influential stakeholders, fostered ownership over the DA and positive emotional associations, spread desirable norms across sites, and situated the DA within established default processes. DA reach to eligible patients increased from 9.8% in the first month of implementation to 70.0% in the sixth month. Larger gains in reach were observed following meetings using MINDSPACE approaches.Limitations. The MINDSPACE framework does not capture all possible influences on behavior and responses to nudges may differ across populations.Conclusions. Behavioral economics can be applied to implementation science to foster uptake of SDM tools by increasing clinician motivation. Our recommendations can help other researchers effectively apply these approaches in real-world settings when there are often limited incentives and opportunities to change organizational- or structural-level factors.